THE CHILD-CENTERED PARADIGM AND ITS IMPLICATIONS FOR THE CONTINUOUS PROFESSIONAL DEVELOPMENT OF EARLY CHILDHOOD TEACHERS - Horațiu CATALANO; Ana RUS; Gabriela MESTIC; Andreea-Ionela DOHOTARU (International Journal of Social and Educational Innovation)
The paradigm of child-centered education involves a fundamental shift in attitude, in which the emphasis shifts from the role of the teacher as the primary provider of knowledge to placing the child at the center of the educational process, as an active participant in his or her own formation. Supporting a child-centered educational process requires a deep understanding of the child's personality in relation to individual and age-specific characteristics.